Time series analysis of factors affecting the demand for local rice in Malaysia - Chung, Bon Hee; Tan, J. R. (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2015)
The own price, income and price of a substitute are the determinants of demand in the classical theory of consumer behavior. We used the theory to analyze the demand for local rice in Malaysia by using time series variables. We examined whether there is a long run relationship among the variables by using the unit root and cointegration tests. We then conducted the Granger causality, variance decomposition and impulse response function tests to examine their directions of causality as well as short term dynamics. The results show that there is a long run relationship among the variables and a unidirectional causality from price and income to demand. There are also lagged and short term dynamics among the variables.